Mg-Y-La alloy and preparation method thereof
By introducing elements such as Y, La, Al2Y and TiB2 into the magnesium alloy, Mg-Y-La alloy is formed, and multi-step process is used to solve the problem of poor mechanical properties of magnesium alloy at room temperature, and the formation of ultrafine crystal structure and significant improvement in mechanical properties are achieved.
Patent Information
- Application Number
- CN202411958658.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-28
AI Technical Summary
Magnesium alloys have poor room temperature mechanical properties, especially in terms of plastic processing properties, and it is difficult to directly form ultrafine crystal magnesium alloys through rotary forging.
The chemical composition of the Mg-Y-La alloy, including Y6.5 to 13.5 wt.%, La 0.45 to 0.75 wt.%, Al2Y 1.35 to 6.06 wt.%, TiB20.15 to 1.05 wt.%, and the remaining amount of Mg is formed by smelting, casting, homogenizing treatment, hot extrusion and rotary forging deformation.
By introducing multi-scale particles and rotary forging deformation, the grain boundaries are effectively pinned, hindering the growth and coarsing of dynamic recrystallization, accumulating more dislocations, promoting dynamic recrystallization of alloys, realizing ultrafine crystallization, and significantly improving the room temperature mechanical properties of Mg-Y-La alloy.
Smart Images

Figure BDA0005216538080000091 
Figure HDA0005216538090000011 
Figure HDA0005216538090000012
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of high-strength magnesium alloy preparation, and particularly relates to a Mg-Y-La alloy and a preparation method thereof. Background Art
[0002] Magnesium alloys have the advantages of low density, high specific strength, and excellent damping and shock absorption performance. They have great application potential in the fields of automobiles, national defense science and technology, aerospace, and electronics. However, the room temperature mechanical properties of lightweight magnesium alloys are poor. Studies have shown that ultrafine-grained magnesium alloys have high strength and can meet the needs of high-precision fields for high-performance magnesium alloys. Endogenous and exogenous multi-scale particles can significantly improve the mechanical properties of magnesium alloys while ensuring that the material has a low density. In terms of deformation technology, rotary forging can generate radial pressure and heat, which is conducive to dynamic recrystallization inside the magnesium alloy material and thus refine the grains. However, magnesium alloys have a close-packed hexagonal crystal structure and poor plastic processing performance. It is difficult to directly form ultrafine-grained magnesium alloys through rotary forging. Therefore, how to effectively introduce a second phase of suitable type, size, and morphology so that it accumulates more dislocations during rotary forging to improve the dynamic recrystallization efficiency and achieve ultrafine-grained magnesium alloys, thereby improving mechanical properties has become a technical problem that needs to be solved in this field. Summary of the invention
[0003] The object of the present invention is to provide a Mg-Y-La alloy and a preparation method thereof. The Mg-Y-La alloy provided by the present invention has excellent mechanical properties.
[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0005] The invention provides a Mg-Y-La alloy, the chemical composition of which comprises, by mass percentage, 6.5-13.5wt.% of Y, 0.45-0.75wt.% of La, 1.35-6.06wt.% of Al2Y, 0.15-1.05wt.% of TiB2 and the balance of Mg.
[0006] Preferably, the chemical composition comprises, by mass percentage, 7-12 wt.% Y, 0.5-0.7 wt.% La, 1.85-5.56 wt.% Al2Y, 0.3-0.9 wt.% TiB2 and the balance Mg.
[0007] The present invention also provides a method for preparing the Mg-Y-La alloy described in the above technical solution, comprising the following steps:
[0008] (1) melting and casting the raw materials in sequence to obtain an ingot;
[0009] (2) homogenizing the ingot obtained in step (1) to obtain an ingot;
[0010] (3) hot extruding the billet obtained in step (2) to obtain an extruded rod;
[0011] (4) The extruded rod obtained in step (3) is subjected to rotary forging deformation to obtain a Mg-Y-La alloy.
[0012] Preferably, the raw materials in step (1) include magnesium, magnesium-yttrium master alloy, magnesium-lanthanum master alloy and TiB2-Al master alloy.
[0013] Preferably, the mass ratio of TiB2 to Al in the TiB2-Al master alloy is (20-40): (60-80).
[0014] Preferably, the smelting temperature in step (1) is 700-750°C.
[0015] Preferably, the casting temperature in step (1) is 700-710°C.
[0016] Preferably, the holding temperature of the homogenization treatment in step (2) is 480-520° C., and the holding time of the homogenization treatment is 10-14 h.
[0017] Preferably, the temperature of hot extrusion in step (3) is 420-480° C., and the extrusion ratio of hot extrusion is (16-20):1.
[0018] Preferably, the feed rate of the rotary forging deformation in step (4) is 2 to 7 mm / min, and the deformation amount of a single pass of the rotary forging deformation is 1.99 to 2.18%.
[0019] The present invention provides a Mg-Y-La alloy, the chemical composition of which includes, by mass percentage, 6.5-13.5wt.% Y, 0.45-0.75wt.% La, 1.35-6.06wt.% Al2Y, 0.15-1.05wt.% TiB2 and the balance Mg. In the present invention, Al2Y and TiB2 act as α-Mg heterogeneous nucleation sites to refine the magnesium alloy structure; at the same time, they can effectively pin the grain boundaries, hinder the growth and coarsening of dynamic recrystallization, and in addition, they can accumulate more dislocations, promote dynamic recrystallization of the alloy, and achieve ultrafine grains; Y will precipitate along the alloy grain boundaries to form a large amount of Y-rich phase, which plays a role in strengthening the second phase; La and Mg will form Mg 12 La particles play a role of second phase strengthening, thereby improving the mechanical properties of the Mg-Y-La alloy. Experimental results show that the yield strength of the Mg-Y-La alloy provided by the present invention is 391-412MPa, the tensile strength is 400-421MPa, and the fracture stress is 2.4-2.6% at room temperature. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a transmission electron microscope image of the Mg-Y-La alloy prepared in Example 2;
[0021] Figure 2 This is a scanning electron microscope image of the Mg-Y-La alloy prepared in Example 3;
[0022] Figure 3 This is a transmission electron microscope image of the Mg-Y-La alloy prepared in Example 2;
[0023] Figure 4 2 are tensile engineering stress-strain curves of the Mg-Y-La alloys prepared in Comparative Example 1 and Examples 1 to 3 at room temperature. DETAILED DESCRIPTION
[0024] The invention provides a Mg-Y-La alloy, the chemical composition of which comprises, by mass percentage, 6.5-13.5wt.% of Y, 0.45-0.75wt.% of La, 1.35-6.06wt.% of Al2Y, 0.15-1.05wt.% of TiB2 and the balance of Mg.
[0025] In terms of mass percentage, the chemical composition of the Mg-Y-La alloy provided by the present invention includes Y6.5-13.5wt%. As an embodiment, the mass percentage of Y can be 7-12wt.%, and can also be 8wt.%, 9wt.%, 10wt.% or 11wt.%. In the present invention, the Y will precipitate along the alloy grain boundaries to form a large amount of Y-rich phase, which plays a role of second phase strengthening.
[0026] In terms of mass percentage, the chemical composition of the Mg-Y-La alloy provided by the present invention further includes La 0.45-0.75 wt.%. As an embodiment, the mass percentage of La can be 0.5-0.7 wt.%, and can also be 0.55 wt.%, 0.6 wt.% or 0.65 wt.%. In the present invention, La and Mg form Mg 12 La particles are mainly distributed at the grain boundaries, playing the role of second phase strengthening and pinning the grain boundaries, thereby improving the mechanical properties of the Mg-Y-La alloy.
[0027] In terms of mass percentage, the chemical composition of the Mg-Y-La alloy provided by the present invention also includes Al2Y1.35-6.06wt.%. As an embodiment, the mass percentage of Al2Y can be 1.85-5.56wt.%, and can also be 2wt.%, 2.5wt.%, 3wt.%, 3.5wt.%, 3.71wt.%, 4wt.%, 4.5wt.%, 5.0wt.% or 5.3wt.%. In the present invention, Al2Y acts as an α-Mg heterogeneous nucleation site to refine the magnesium alloy structure; at the same time, it can effectively pin the grain boundary, hinder the growth and coarsening of dynamic recrystallization, and in addition, it can accumulate more dislocations, promote dynamic recrystallization of the alloy, and achieve ultrafine grains.
[0028] In terms of mass percentage, the chemical composition of the Mg-Y-La alloy provided by the present invention further includes TiB20.15-1.05wt.%. As an embodiment, the mass percentage of the TiB2 can be 0.3-0.9wt.%, and can also be 0.4wt.%, 0.5wt.%, 0.6wt.%, 0.7wt.% or 0.8wt.%. In the present invention, TiB2 acts as an α-Mg heterogeneous nucleation site to refine the magnesium alloy structure; at the same time, it can effectively pin the grain boundary, hinder the growth and coarsening of dynamic recrystallization, and in addition, it can accumulate more dislocations, promote dynamic recrystallization of the alloy, and achieve ultrafine grains.
[0029] In terms of mass percentage, the chemical composition of the Mg-Y-La alloy provided by the present invention also includes a balance of Mg. In the present invention, the Mg is a matrix element.
[0030] In the present invention, Mg in the Mg-Y-La alloy 12 The diameter of La is preferably 1.8 to 3.4 μm, the diameter of Al2Y is preferably 1.2 to 57.3 μm, and the diameter of TiB2 is preferably 88.3 to 106.4 nm.
[0031] In the present invention, Al2Y and TiB2 act as α-Mg heterogeneous nucleation sites to refine the magnesium alloy structure; at the same time, they can effectively pin the grain boundaries, hinder the growth and coarsening of dynamic recrystallization, and in addition, they can accumulate more dislocations, promote dynamic recrystallization of the alloy, and achieve ultrafine grains; Y will precipitate along the alloy grain boundaries to form a large amount of Y-rich phase, which plays a role in strengthening the second phase; La and Mg will form Mg 12 La particles play the role of second phase strengthening, thereby improving the mechanical properties of Mg-Y-La alloy.
[0032] The present invention also provides a method for preparing the Mg-Y-La alloy described in the above technical solution, comprising the following steps:
[0033] (1) melting and casting the raw materials in sequence to obtain an ingot;
[0034] (2) homogenizing the ingot obtained in step (1) to obtain an ingot;
[0035] (3) hot extruding the billet obtained in step (2) to obtain an extruded rod;
[0036] (4) The extruded rod obtained in step (3) is subjected to rotary forging deformation to obtain a Mg-Y-La alloy.
[0037] The present invention has no particular limitation on the sources of the raw materials, and commercially available products known to those skilled in the art may be used.
[0038] The invention sequentially smelts and casts raw materials to obtain ingots.
[0039] In the present invention, the raw materials preferably include magnesium, magnesium-yttrium master alloy, magnesium-lanthanum master alloy and TiB2-Al master alloy.
[0040] In the present invention, the purity of the magnesium is preferably ≥99.8%; the purity of the magnesium-yttrium master alloy is preferably ≥99.9%; the mass content of yttrium in the magnesium-yttrium master alloy is preferably 20-40%, more preferably 30%; the purity of the magnesium-lanthanum master alloy is preferably ≥99.9%; the mass content of lanthanum in the magnesium-lanthanum master alloy is preferably 20-40%, more preferably 30%.
[0041] In the present invention, the mass ratio of TiB2 to Al in the TiB2-Al master alloy is preferably (20-40): (60-80), more preferably 30:70; the average size of the TiB2 is preferably 88.3-106.4 nm, more preferably 98 nm.
[0042] In the present invention, the preparation method of the TiB2-Al master alloy is preferably to mix TiB2 with aluminum powder, and then perform hot pressing and sintering to obtain the TiB2-Al master alloy.
[0043] The present invention has no particular limitation on the particle size of the aluminum powder, and any aluminum powder well known to those skilled in the art may be used.
[0044] In the present invention, the mixing is preferably ball milling; the rotation speed of the ball mill is preferably 90-110 r / min, more preferably 100 r / min; the ball-to-material ratio of the ball mill is preferably (2-4):1, more preferably 3:1.
[0045] In the present invention, the temperature of the hot pressing sintering is preferably 660-850°C, more preferably 800°C; the temperature of the hot pressing sintering is preferably 5-30s, more preferably 15-20s; the rate of heating to the hot pressing sintering temperature is preferably 20-35K / min, more preferably 25-30K / min; the pressure of the hot pressing sintering is preferably 45-55MPa, more preferably 50MPa.
[0046] In the present invention, the mass ratio of the magnesium, the yttrium content in the magnesium-yttrium master alloy, the lanthanum content in the magnesium-lanthanum master alloy and the TiB2-Al master alloy is preferably (82.8-92.1): (6.5-13.5): (0.45-0.75): (1-3), and more preferably (88.4-89.4): 9: 0.6: 1.
[0047] The present invention has no special limitation on the mixing operation of the magnesium, magnesium-yttrium master alloy, magnesium-lanthanum master alloy and TiB2-Al master alloy, and the technical scheme for preparing the mixed material well known to those skilled in the art can be adopted.
[0048] In the present invention, the smelting is preferably carried out in a protective gas; the protective gas is preferably CO2 and SF6; the volume ratio of CO2 and SF6 is preferably (98-99): (1-2), more preferably 99: 1. In the present invention, the protective gas can prevent oxidation during the smelting process and improve the purity and quality of the magnesium alloy.
[0049] In the present invention, the smelting is preferably carried out under stirring conditions; the stirring time is preferably 15 to 20 minutes. The present invention has no special limitation on the stirring rate, and the operation well known to those skilled in the art can be adopted.
[0050] As an implementation manner, the stirring time may be 16 to 18 minutes.
[0051] In the present invention, the smelting temperature is preferably 700-750° C. As an embodiment, the smelting temperature may be 710-740° C., or 720-730° C.
[0052] After the smelting is completed, the present invention preferably removes the slag from the product obtained by the smelting.
[0053] The present invention has no particular limitation on the deslagging operation, and operations well known to those skilled in the art may be adopted.
[0054] In the present invention, the casting temperature is preferably 700-710° C. As an embodiment, the casting temperature may be 705-708° C.
[0055] In the present invention, the diameter of the ingot is preferably 80-90 mm, more preferably 85 mm.
[0056] After obtaining the ingot, the present invention performs homogenization treatment on the ingot to obtain a billet.
[0057] In the present invention, the holding temperature of the homogenization treatment is preferably 480-520°C, more preferably 500°C; the holding time of the homogenization treatment is preferably 10-14h, more preferably 12h. The present invention limits the process parameters of the homogenization treatment to the above range, which can further improve the mechanical properties of the Mg-Y-La alloy.
[0058] In the present invention, the cooling method of the homogenization treatment is preferably air cooling. The present invention has no special limitation on the operation of the air cooling, and air cooling to room temperature can be performed by an operation well known to those skilled in the art.
[0059] After obtaining the billet, the present invention performs hot extrusion on the billet to obtain an extruded rod.
[0060] In the present invention, the temperature of the hot extrusion is preferably 420-480° C., more preferably 440° C.; the extrusion ratio of the hot extrusion is preferably (16-20):1, more preferably 18:1.
[0061] In the present invention, the diameter of the extruded rod is preferably 16 to 25 mm, more preferably 20 mm.
[0062] After the extruded rod is obtained, the present invention performs rotary forging deformation on the extruded rod to obtain the Mg-Y-La alloy.
[0063] In the present invention, the feed rate of the rotary forging deformation is preferably 2-7 mm / min; the deformation amount of the rotary forging deformation in a single pass is preferably 1.99-2.18%; and the number of passes of the rotary forging deformation is preferably 16-24. The present invention adopts multi-pass rotary forging deformation to effectively break up micron Al2Y particles, and a large number of dislocations are gathered in Al2Y particles and nano-TiB2 particles, promoting dynamic recrystallization, so that the alloy reaches ultrafine grains; at the same time, it promotes the precipitation of a large number of Y-rich phases along the grain boundaries of the alloy, which plays a role in strengthening the second phase.
[0064] As an implementation mode, the feed rate of the rotary forging deformation can be 3-6 mm / min, or 4-5 mm / min; the deformation amount of a single rotary forging deformation can be 2-2.15%; the number of rotary forging deformation passes can be 18-22 passes, or 20 passes.
[0065] In the present invention, the diameter of the Mg-Y-La alloy is preferably 14 to 22 mm, more preferably 18 mm.
[0066] In the present invention, during the melting, casting and solidification process, the micron Al2Y particles and the nano-TiB2 particles can be used as α-Mg heterogeneous nucleation sites to refine the alloy structure; during extrusion, the micron Al2Y particles and the nano-TiB2 particles can effectively pin the grain boundaries, hindering the growth and coarsening of dynamic recrystallization; during rotary forging, the coarse micron Al2Y particles can be effectively broken, and the Al2Y particles and the nano-TiB2 particles can accumulate more dislocations during the rotary forging process, promoting the dynamic recrystallization of the composite material and achieving ultrafine grains; at the same time, rotary forging promotes the precipitation of a large amount of Y-rich phase along the grain boundaries of the alloy, playing a role in second phase strengthening, thereby significantly improving the room temperature mechanical properties of the Mg-Y-La alloy, which is conducive to expanding the application of rare earth magnesium alloys in key components in the fields of aerospace and national defense.
[0067] The present invention combines nano TiB2 ceramic particles and micron-sized Mg 12 La particles were introduced into the alloy, and in-situ micronized Al2Y particles were generated. At the same time, the alloy structure was further refined by rotary forging deformation and precipitation strengthening was performed, which significantly improved the room temperature mechanical properties of the Mg-Y-La alloy and expanded the application of magnesium alloys as key components in the aerospace and defense fields. Micronized Mg was introduced into the Mg-Y-La alloy by adding Mg-Y, Mg-La master alloy and TiB2-Al master alloy. 12 La particles and nano-TiB2 particles react to generate in-situ micronized Al2Y particles; among them, Al2Y particles can be generated by adding Al element to Mg-Y alloy. The two-dimensional lattice mismatch between Al2Y particles and magnesium matrix is 6.5%, and the phase relationship is (044) Al2Y / / (0002) α-Mg; Al2Y particles can refine the alloy structure as heterogeneous nucleation cores and improve the distribution of Mg-RE phase; the solid solubility of La element in Mg is very limited (0.03wt.% at 500℃), mainly in the form of Mg. 12 La phase exists in the α-Mg grain boundary; during hot working and heat treatment, Mg 12 The La phase inhibits the growth and coarsening of α-Mg grains by pinning the grain boundaries; nano-TiB2 particles have the characteristics of low density, high hardness, and high melting point. When introduced into magnesium alloys, they can strengthen the alloy by hindering dislocation movement and grain boundary sliding, thereby improving the mechanical properties of magnesium alloys.
[0068] In the smelting preparation process, the present invention can obtain nano TiB2 particles, micron-sized Al2Y particles and Mg2O3 particles with good dispersibility without using additional ultrasonic dispersion. 12 The Mg-Y-La alloy material synergistically strengthened by La particles has a simple preparation process, is easy to promote, and has good application prospects.
[0069] The present invention can effectively break large block and long needle-shaped Al2Y particles during rotary forging deformation. At the same time, rotary forging deformation generates greater pressure and heat during processing, which is beneficial to dynamic recrystallization inside the material to achieve grain refinement and promote the precipitation of the second phase to jointly improve the mechanical properties of the material.
[0070] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0071] The Mg-30wt.% Y and Mg-30wt.% La used in the embodiment were purchased from Chongqing Yuhua New Materials Technology Co., Ltd.; TiB2 was purchased from Shanghai Xiangtian Nanomaterials Co., Ltd., with a size of 88.3-106.4nm (average size of 98nm); pure aluminum powder was purchased from Beijing Xingrongyuan Technology Co., Ltd., with a size of 8.6-14.2μm (average size of 10μm) and a purity of 99.5%.
[0072] Example 1
[0073] The chemical composition of the Mg-Y-La alloy is as follows by mass percentage: Y 9wt.%, La 0.6wt.%, Al2Y1.85wt.%, TiB20.3wt.% and the balance Mg;
[0074] The preparation method of the Mg-Y-La alloy comprises the following steps:
[0075] (1) Pure magnesium with a purity of 99.8% is melted in a resistance furnace at 720° C. under protective gas, and then Mg-30wt.%Y with a purity of 99.9%, Mg-30wt.%La with a purity of 99.9% and TiB2-Al master alloy are added and melted at 720° C., and the mixture is stirred for 17 minutes under heat preservation for smelting, and after slag removal, the mixture is cast at 705° C. to obtain an ingot with a diameter of 85 mm; wherein the preparation method of the TiB2-Al master alloy is as follows: TiB2 with a mass ratio of 30:70 is added; The product is obtained by ball milling with pure aluminum powder and hot pressing and sintering at 800°C for 15s; the rotation speed of the ball mill is 100r / min, and the ball-to-material ratio is 3:1; the rate of heating to 800°C is 25K / min, and the pressure of hot pressing and sintering is 50MPa; the protective gas is composed of 99% CO2 and 1% SF6; the mass ratio of pure magnesium, yttrium content in Mg-30wt.%Y, lanthanum content in Mg-30wt.%La and TiB2-Al master alloy is 89.4:9:0.6:1;
[0076] (2) homogenizing the ingot obtained in step (1) at 520° C. for 12 h, and then air-cooling to room temperature to obtain an ingot;
[0077] (3) hot extruding the billet obtained in step (2) at 420° C. with an extrusion ratio of 18:1 to obtain an extruded rod with a diameter of 20 mm;
[0078] (4) The extruded rod obtained in the step (3) is subjected to rotary forging deformation, the feed speed is controlled to be 5 mm / min, the deformation amount per pass is 2.15%, the number of rotary forging deformation passes is 20 passes, and a Mg-Y-La alloy with a diameter of 18 mm is obtained; the Mg-Y-La alloy is (1.85wt.%Al2Y+0.3wt.%TiB2) / Mg-9Y-0.6La.
[0079] Example 2
[0080] The chemical composition of the Mg-Y-La alloy is as follows by mass percentage: Y 9wt.%, La 0.6wt.%, Al2Y3.71wt.%, TiB20.6wt.% and the balance Mg;
[0081] The preparation method of the Mg-Y-La alloy is based on Example 1, and the mass ratio of pure magnesium, yttrium content in Mg-30wt.%Y, lanthanum content in Mg-30wt.%La and TiB2-Al intermediate alloy is changed to 88.4:9:0.6:2; the single-pass deformation amount of rotary forging deformation is 2.1%, and other conditions remain unchanged, and the obtained Mg-Y-La alloy is (3.71wt.%Al2Y+0.6wt.%TiB2) / Mg-9Y-0.6La.
[0082] Example 3
[0083] The chemical composition of the Mg-Y-La alloy is as follows by mass percentage: Y 9wt.%, La 0.6wt.%, Al2Y5.56wt.%, TiB20.9wt.% and the balance Mg;
[0084] The preparation method of the Mg-Y-La alloy is based on Example 1, and the mass ratio of pure magnesium, yttrium content in Mg-30wt.%Y, lanthanum content in Mg-30wt.%La and TiB2-Al intermediate alloy is changed to 87.4:9:0.6:3; the single-pass deformation amount of rotary forging deformation is 2.0%, and other conditions remain unchanged, and the obtained Mg-Y-La alloy is (5.56wt.%Al2Y+0.9wt.%TiB2) / Mg-9Y-0.6La.
[0085] Comparative Example 1
[0086] The chemical composition of the Mg-9Y-0.6La matrix alloy is as follows by mass percentage: Y 9wt.%, La 0.6wt.% and the balance Mg;
[0087] The preparation method of the Mg-9Y-0.6La matrix alloy is the same as that in Example 1, and the raw materials are adjusted as needed.
[0088] The multi-scale particles in the Mg-Y-La alloys of Examples 1 to 3 are Al2Y micron particles, Mg 12 La micron particles and TiB2 nanoparticles, among which Mg 12 The diameter of La micron particles is 1.8-3.4 μm, the diameter of Al2Y micron particles is 1.2-57.3 μm, and the diameter of TiB2 nanoparticles is 88.3-106.4 nm.
[0089] The structure and performance of the alloys prepared in Examples 1 to 3 and Comparative Example 1 were analyzed as follows:
[0090] 1. Microstructure analysis
[0091] Figure 1 This is a transmission electron microscope image of the Mg-Y-La alloy prepared in Example 2.
[0092] from Figure 1 It can be seen that Al2Y particles exist at the grain boundaries, a large number of ultrafine grains are present inside the Mg-Y-La alloy, and the average grain size of α-Mg is 694nm.
[0093] Figure 2 This is a scanning electron microscope image of the Mg-Y-La alloy prepared in Example 3.
[0094] from Figure 2 It can be seen that due to the large pressure and heat generated by rotary forging deformation during processing, the large Al2Y particles inside 5.56wt.%Al2Y+0.9wt.%TiB2) / Mg-9Y-0.6La were broken, and there were no cracks at the interface with the matrix, achieving metallurgical bonding with the matrix; the broken large Al2Y particles are beneficial to reducing stress concentration during the tensile process and improving the mechanical properties of the Mg-Y-La alloy.
[0095] Figure 3 This is a transmission electron microscope image of the Mg-Y-La alloy prepared in Example 2.
[0096] from Figure 3 It can be seen that the introduction of Al2Y-TiB2 particles is beneficial to promote the precipitation of a large number of second phases at the grain boundaries of the Mg-Y-La alloy, mainly Y-phase-rich particles, which is beneficial to improve the strength of the Mg-Y-La alloy during the tensile process, but will reduce the plasticity.
[0097] 2. Room temperature strength test
[0098] Figure 4 The tensile engineering stress-strain curves of the Mg-Y-La alloys prepared in Comparative Example 1 and Examples 1 to 3 at room temperature, and the obtained yield strength, tensile strength and fracture strain results are shown in Table 1.
[0099] Table 1 Performance data of Mg-Y-La alloys prepared in Comparative Example 1 and Examples 1 to 3 at room temperature
[0100]
[0101] Test method: Testing machine (CMT5105-100 KN), tensile strain rate 1×10 -3 s -1 ; The total length of the tensile specimen is 48mm, and the standard cross-sectional dimensions are 18×4×2mm 3 .
[0102] It can be seen from Table 1 that compared with Comparative Example 1, the room temperature yield strength and tensile strength of the Mg-Y-La alloy prepared in Example 2 are increased by 62 MPa and 53 MPa, respectively, indicating that the endogenous and exogenous multi-scale Al2Y-TiB2 particles effectively improve the room temperature mechanical properties of the Mg-9Y-0.6La alloy.
[0103] In summary, in the present invention, firstly, during the melting, pouring and solidification process, the micron Al2Y particles and the nano-TiB2 particles can serve as α-Mg heterogeneous nucleation sites to refine the alloy structure; during extrusion, the micron Al2Y particles and the nano-TiB2 particles can effectively pin the grain boundaries, hindering the growth and coarsening of dynamic recrystallization; during rotary forging deformation, large pieces of endogenous micron Al2Y particles can be effectively broken, and the Al2Y particles and the nano-TiB2 particles can accumulate more dislocations during the rotary forging process, promoting recrystallization and refining the alloy structure; at the same time, the introduction of Al2Y-TiB2 particles promotes the precipitation of a large amount of Y-rich phase along the grain boundaries of the Mg-Y-La alloy, playing a role of second phase strengthening, so that the Mg-Y-La alloy obtains a high fine grain strengthening effect and the Al2Y micron particles and Mg 12 La micron particles, Y-rich phase particles and TiB2 nanoparticles improve the mechanical properties of Mg-Y-La alloy by pinning dislocation motion and hindering grain boundary sliding.
[0104] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A Mg-Y-La alloy, the chemical composition of which, by mass percentage, comprises: Y 6.5~13.5wt.%, La 0.45~0.75wt.%, Al2Y 1.35~6.06wt.%, TiB2 0.15~1.05wt.% and the balance Mg.
2. The Mg-Y-La alloy according to claim 1, characterized in that The chemical composition comprises, by mass percentage, 7-12 wt.% of Y, 0.5-0.7 wt.% of La, 1.85-5.56 wt.% of Al2Y, 0.3-0.9 wt.% of TiB2 and the balance of Mg.
3. The method for preparing the Mg-Y-La alloy according to claim 1 or 2, comprising the following steps: (1) melting and casting the raw materials in sequence to obtain an ingot; (2) homogenizing the ingot obtained in step (1) to obtain an ingot; (3) hot extruding the billet obtained in step (2) to obtain an extruded rod; (4) The extruded rod obtained in step (3) is subjected to rotary forging deformation to obtain a Mg-Y-La alloy.
4. The preparation method according to claim 3, characterized in that: The raw materials in step (1) include magnesium, magnesium-yttrium master alloy, magnesium-lanthanum master alloy and TiB2-Al master alloy.
5. The preparation method according to claim 4, characterized in that: The mass ratio of TiB2 to Al in the TiB2-Al master alloy is (20-40): (60-80).
6. The preparation method according to claim 3, characterized in that: The smelting temperature in step (1) is 700-750°C.
7. The preparation method according to claim 3, characterized in that: The casting temperature in step (1) is 700-710°C.
8. The preparation method according to claim 3, characterized in that: The heat preservation temperature of the homogenization treatment in the step (2) is 480-520° C., and the heat preservation time of the homogenization treatment is 10-14 hours.
9. The preparation method according to claim 3, characterized in that: The temperature of the hot extrusion in the step (3) is 420-480° C., and the extrusion ratio of the hot extrusion is (16-20):
1.
10. The preparation method according to claim 3, characterized in that: In the step (4), the feed rate of the rotary forging deformation is 2-7 mm / min, and the deformation amount of a single pass of the rotary forging deformation is 1.99-2.18%.
Citation Information
Patent Citations
Preparation method of ultralight high-plasticity magnesium-lithium alloy bar
CN118957330A